The Influence Of Marketing Mix On Marketing Performance In Tye Coffe House Surabaya - Pratama, Caesariano Afrilio; Widayanti, Sri; Fitriana, Nisa Hafi Idhoh (Jurnal Agribest, 2024)
Tye Coffee House is a contemporary coffee shop that offers a variety of high quality coffee and non-coffee drinks. As the number of coffee shops in Surabaya increases nowadays. Tye Coffee House implements various marketing mixes so that sales can survive in an increasingly competitive market. The aim of this research is to describe the 7P marketing components that have been implemented by Tye Coffee House, analyze the marketing mix and marketing performance on consumer perceptions at Tye Coffee House Surabaya, analyze the influence of the marketing mix and marketing performance at Tye Coffee House Surabaya. The method in this research uses descriptive analysis and the WarpPLS 8.0 analysis tool with 50 Tye Coffe House Surabaya consumer respondents. The results of the research show that the 7P marketing mix components carried out by Tye Coffee House are considered good by the majority of consumers and in testing the 7P marketing mix on Tye Coffee House's marketing performance it was found that there were 6 marketing mix components in this study that had a significant effect on the acceptance of the research hypothesis and one mix component other marketers rejected their research hypothesis.